Farmer Empowerment Model for Climate Change Anticipation - Sumastuti, Efriyani; Pradono, Nuswantoro Setyadi (Universitas Negeri Semarang, 2018)
The purpose of this research is to arrange an empowerment model for farmers of prime food crops in order to anticipate climate change in Central Java. The data used are primary ones collected through in-depth interviews with key persons and via Focus Group Discussion (FGD), which later went through Analysis Hierarchy Process (AHP). To formulate an empowerment model for farmers of prime food crops, reconstructions of existing field findings were performed based on FGD results and in-depth interviews with key persons and several related institutions. The results of research showed that in order to anticipate climate change, there are three main priorities that should be taken. They are: (1) to conduct anticipations towards climate change; (2) to deliver aids in production technology in accordance with the ocurrence of climate change and (3) to deliver information regarding planting time and types of crop.